Assertiveness in family nurses - Machado, Dora (2023)
Assertiveness is a crucial social skill for effective and efficient communication in nursing (Montezeli et al., 2018). At the professional level, its lack can generate conflicts, frustrations and loss of essential information, compromising the care process (Silva, 2018). In contrast, becoming more assertive contributes to the success of the therapeutic relationship with users and families, by promoting: greater recognition and respect for the nurse as a person and professional; greater satisfaction in the performance of tasks and in the relationship with the team and the user; and also greater security for the user (Haladin et al., 2015; Nakamura et al., 2017; Omura et al., 2017). In addition, it can protect nurses from the daily pressure to which they are exposed and from situations that trigger stress and depression (Alves, 2016). The World Health Organization (WHO, 2016) recognizes assertive communication as essential in the global challenge for patient safety.